Impacts of professional sports stadium development projects on urban areas - Corwin, Charles S. (Kansas State University, 2011)
Professional sports stadium development projects are major civic endeavors, and city officials and sports franchises often promise stadiums will generate significant gains in the regional economy. This study examines the effectiveness of stadium development in inducing economic development and urban revitalization by conducting a secondary data analysis, and case study of PNC Park and Heinz Field in Pittsburgh, Pennsylvania. Consistent with prior empirical studies, the secondary data analysis shows that stadium projects do not always produce significant regional economic benefits. A close investigation of the two stadium projects in the North Shore neighborhood of Pittsburgh, however, finds substantially positive effects on investment and physical development at the district level. The present research suggests that stadium developments can be a more powerful urban redevelopment catalyst when consideration is given to four essential factors – location, design, institutional structure, and history and timing.
Keywords: Sports stadium development; Urban revitalization; Economic development; Physical development; Area Planning and Development (0341); Urban Planning (0999)